FACING FLOODS IN TÉBESSA CITY, EASTERN ALGERIA, A MORPHOMETRIC AND CARTOGRAPHIC APPROACH TO PRIORITIZE INTERVENTION IN THE CITY'S SUB-WATERSHEDS USING GIS AND REMOTE SENSING - Hadjela, A; Annab, R; Seghir*, K (university of el oued/جامعة الوادي, 2021)
The objective of this work is to determine the importance of the five partial sub-watersheds that penetrate the city of Tébessa and their water networks in the “Oued El Kabir” watershed , belonging to the semi-arid climate Characterized by torrential rains constituting a natural danger, in terms of the real dimensions of the floods, especially since the hydromorphological characteristics of the valleys are not clear on the ground, because of the urban expansion which carried them away. The study was based on the morphometric and cartographic approach which allows the comparison of sub-watersheds between them, through 12 indicators, to determine the most influential sub- watersheds using GIS and remote sensing The results showed that the “ennagues” sub-watershed is the most dangerous for the city, it is a priority for its protection, and the need to manage the most vulnerable parts
Article
Keywords: sub watershed; Tébessa city; flood; morphometric; natural danger